Dental training in evidence-based dentistry: A replication study - Stefanie Dreher; Tobias Weberschock; Maria Giraki; Alexander Uhse; Puria Parvini; Stefan Rüttermann; Susanne Gerhardt-Szep (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Background: In the area of education research, it is well-known that studies of a defined question are seldom replicated. Furthermore, e-learning resources with evidence-based content in dentistry have received relatively little attention from researchers. The Context and Purpose of the Study: The aim of this clinical study was to evaluate how dentistry students from two consecutive cohorts in their first clinical semester rate a long-standing evidencebased dentistry (EbD) resource in an e-learning environment using a questionnaire of 43 specific items on 1) general questions regarding user-friendliness and acceptability, as well as 2) specific questions on content and functional range (A), handling and technical aspects (B), and didactics and educational value(C) based on a Likert scale from 0 = 'strongly disagree' to 3 = 'strongly agree', and how this compares to a primary study in which the resource was addressed as a novelty. The data were analyzed statistically using a one-way ANOVA followed by a Kruskal-Wallis multiple-comparison Z-test. Results: A response rate of 100% was achieved. The majority of the users thought the topic of EbD to be important. The e-learning resource was rated with a score of 2.40 ± 0.66 (on a Likert scale from 1-6 where 1 = "very good" and 6 = "insuffi cient"). 86.15% of the students stated that they consider the resource beneficial for their study in clinical simulation and in patient treatment courses. The results averaged for A: 1.92 (±0.57; median: 1.928), B: 1.48 (±0.60), and C: 2.27 (±0.67). The obtained results in the replication study showed no statistical significant differences to the primary study. Conclusions: The e-learning resource with dentistry vignettes cases and learning components on evidence-based principles was consistently rated positively by the students. Owing to their agreement with the data of the primary study, the results of the present study point to the remarkable validity of the method of evaluation. This should be addressed in future studies with larger cohorts.